STUDI LIMIT DIAMETER PADA SISTEM TEBANG PILIH HUTAN ALAM - Hariyatno Dwiprabowo (Jurnal Penelitian Hasil Hutan, 1990)
Indonesian Selective Cutting (Tebang Pilih  Indonesia) as a silviculture  system  pays  a  considerable  attention to the growth  of seedlings  and saplings in  the forests  as it is considered  to represent  the fourth generation  in the succession  of the  tropical  rain forests. However, there is some question as to how  to relate  the growth  to the detennination   of cutting diameter   limit  quantitatively   such  that  in detennining   the diameter  limit  the growth  of  the seedlings can  be. part  of  the objective  to be considered.With  regard  to  this  problem a  study was conducted  in S. Seruyan Hulu  and  S.  Jelang - S. Delai  forests, Central Kalimantan, to examine the relationship between the height  of seedlings of  meranti  species  (Shorea  spp.)  and tress basal area in several sample  plots.   The  relationship  expressed   in  a  polynomial  regression equation  then  was used  to find  the optimal  diameter  limits  with a criterion  of maximizing   the height  of the seedlings.The  study showed   that  the optimal  diameter  limit  was dependent   upon  the  trees basal area and  the distribution  of trees diameters  of the stand.